Analisis Pengaruh Stres Kerja Terhadap Turnover Intention Pada Karyawan Gen Z Di Pt Busana Remaja Agracipta Kalasan - Maria Nofriyanti (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of job stress on turnover intention in Generation Z employees at PT Busana Remaja Agracipta Kalasan. This research uses a quantitative approach. The type and source of data used are primary data. The data analysis technique used in this research is simple linear regression, namely Y = 13.242 + 0.466X. The results of simple linear regression analysis show that job stress has a positive and significant effect on turnover intention, with a significance value of 0.001 <0.05 and a value of 3.580 greater than the value of 1.997, it can be concluded that HO is rejected and H1 is accepted. The coefficient of determination (R²) value of 0.152 indicates that job stress explains 15.2%, the turnover intention variable and the rest is influenced outside the study.